2016
DOI: 10.1016/j.healthplace.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of socioeconomic, biogeophysical and built environment on old-age survival in a Southern European city

Abstract: Old-age survival is a good indicator of population health and regional development. We evaluated the spatial distribution of old-age survival across Porto neighbourhoods and its relation with physical (biogeophysical and built) and socioeconomic factors (deprivation). Smoothed survival rates and odds ratio (OR) were estimated using Bayesian spatial models. There were important geographical differentials in the chances of survival after 75 years of age. Socioeconomic deprivation strongly impacted old-age surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
1
15
0
1
Order By: Relevance
“…This result was unexpected considering that previous studies have shown that maternal socio‐economic status is associated with initiation and duration of breast milk feeding in very preterm infants . However, the European Deprivation Index is a validated and robust measure with very fine geographical scales and was used in other studies with Portuguese data that reported associations with different outcomes …”
Section: Commentmentioning
confidence: 93%
See 1 more Smart Citation
“…This result was unexpected considering that previous studies have shown that maternal socio‐economic status is associated with initiation and duration of breast milk feeding in very preterm infants . However, the European Deprivation Index is a validated and robust measure with very fine geographical scales and was used in other studies with Portuguese data that reported associations with different outcomes …”
Section: Commentmentioning
confidence: 93%
“…31,36 However, the European Deprivation Index is a validated and robust measure with very fine geographical scales and was used in other studies with Portuguese data that reported associations with different outcomes. 52,53 Regarding our systematic literature review, a considerable heterogeneity was observed across the studies, not allowing us to conduct a meta-analysis. It is difficult to compare the findings of studies on breast milk feeding prevalence due to the different definitions of breast milk feeding used-only breast feeding or breast and bottle feeding; the misclassification of exclusive breast milk feeding; the different periods of assessment-during hospital stay, at or after hospital discharge; and the use of chronological/corrected age when reporting the duration.…”
Section: Limitations Of the Datamentioning
confidence: 99%
“…The spatial distribution of the areas by socioeconomic status (SES) follows a demarcated pattern–areas with similar levels of deprivation tend to be close to each other–revealing a high degree of socio-spatial. Porto also presents a compact urban design (relatively high residential density with mixed land uses) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the Portuguese context, several studies have found large socioeconomic inequalities in health in Portuguese settings [ 48 ], and specifically in Porto municipality [ 18 , 49 ], which despite being relatively small in territorial extent, holds important socioeconomic disparities and presents a high degree of socio-spatial segregation, as most of the population and neighbourhoods are situated either in the least or in the most deprived areas [ 49 , 50 ]. Also, the urbanization process that accelerated after the 20th century in the city caused fragmentation and discontinuity in the green infrastructure, meaning that in only a century, Porto transformed from a “green city” (76% of the city was covered by green area in 1892) to a “grey city” (29% in 2000) [ 51 ].…”
Section: Introductionmentioning
confidence: 99%